REVIEW PENELITIAN TENTANG EARNINGS MANAGEMENT TERHADAP KINERJA PERUSAHAAN - Puji Astuti, Dewi Saptantinah (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2009)
Abstract Finance Information to company represent one of the information regarding hit the condition of company especially information having the character of finance, the information elementary serve the purpose of in performance assessment of an company. relevant information in obtainable performance assessment from balance report, because during the time size measure of erformance relied on by a profit acquirement of company report of company Balance of be of benefit to investor especially for the decision making of invesment, this matter relate to the return expected will be obtained by investor (return ekspektasi). For the reason management try to arrange the profit presented, that is by improving profit reported so that company performance seen nicely. The action recognized by earnings is management. here are some definition of concerning earnings management and also some research of related to this earnings management, breakdown of in detail regarding the earnings management and also issue of related to earnings management will be presented at solution shares. Intention of this article writing is mereview of some research of concerning earnings management, and finally from some the review research of dambil conclusion of about this earnings management will be able to influence the performance of an company. Keywords : company performance, earning management